Women's Involvement in Local Politics? Realizing Reinforcement of Gender Equality in Sinjai Regency, Indonesia - Arief, Aulia Ramdhani; Mustari, Nuryanti; Khaerah, Nur (Journal of Contemporary Local Politics, 2022)
The purpose of this research is related to the strategy of the local government to build gender equality in the political field in Sinjai Regency to determine the Strengthening of the Existence of Women in the Political Sector to Achieve Gender Equality in Sinjai Regency.. The type of this research is qualitative research. This research uses descriptive research. The results of this study are to strengthen the existence of the women in political view to achieve gender equality in Sinjai, the implementation of these policies through Government Regulation number 12 of 2013 concerning Gender Mainstreaming which becomes the foundation and encouragement to be more gender-responsive, and the capability in political already increasing, because there is no more gender discrimination in leadership because already depending on women's capacity and performance, and then the accessibility of the women to access politics has been given a lot of form from government and the legislative. However, patriarchal values become the dominant cultural barrier limiting women's participation in politics.